THE INFLUENCE OF PEER TUTORS ON STUDENTS' LEARNING INTEREST AT SMPN 19 CITY JAMBI - Vina Puspita Sari; Rasimin Rasimin; Affan Yusra (SUJANA: Education and Learning Review, 2023)
The purpose of this study was to measure the influence of peer tutors on students' learning interests at SMPN 19 Kota Jambi. The type of research in this study is quantitative using the ex post-facto method. The number of students who were sampled in this study were 72 students consisting of grades VII and VIII using the Total Sampling technique. the tool used to collect data is the questionnaire instrument. The results of this study indicate that there is an influence of peer tutors on learning interests. The constant acquisition value is 16,588, which means that if the peer tutor variable has a value of 0 then the interest in learning has a value of 16,588. peer tutors experience an increase of one unit, the interest in learning will increase by 0.859 at a constant of 16.588. Next, to test the hypothesis, the t test has criteria, namely if t count ≥ t table then Ha is accepted and Ho is rejected. The t table value at the significant level is 0.05 and dk n-2 is 1.666. the results of the t test using SPSS, namely the value of t count ≥ t table, namely 11,358 ≥ 1,666 then Ha is accepted Ho is rejected meaning "There is an Influence of Peer Tutors on Student Learning Interests at SMPN 19 Jambi City"